The Difference between hs-CRP and Serum IL-6 Levels in Patients with Glaucoma and Non Glaucoma - Muhammad Riduan1, Endang Retnowati Kusumowidagdo1, Nurwasis1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Glaucoma is a group of eye diseases that have the characteristic of optic nerve damage with a specific pattern and field loss of view with or without increased intraocular pressure (IOP). The objective of the study was to analyze the association between glaucoma incidence with hs-CRP and IL-6 levels. Method: This study used patients who fulfilled the inclusion criteria. Inclusion criteria were in the form of patients with a primary closed-angle diagnosis, willing to participate in the research. The study was conducted in the period from March to August 2013. The research procedure included patient examination, hsCRP and IL-6 level examination. Results: Mann-Whitney test result showed difference of hs-CRP with p value of 0.755 and difference of IL-6 level with p = 0.95. Thus, there was no significant difference in the levels of hs-CRP and IL-6 in patients with glaucoma and non-glaucoma. Conclusion: Hs-CRP and serum IL-6 levels in the glaucoma group did not differ from the non-glaucoma group.